Pengaruh Pemberian Ekstrak Bawang Dayak terhadap Delayed Onset Muscle Soreness (DOMS) Ditinjau dari Kadar TNF-α: The Effect of Dayak Onion Extract on Delayed Onset Muscle Soreness (DOMS) in Terms of TNF-α Levels - Aulia Ramadhani; Hilda Carmitha Panjaitan; Fathurrahman Fathurrahman (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2024)
Excessive physical activity can cause Delayed Onset Muscle Soreness (DOMS), associated with oxidative stress and inflammation. One inflammatory marker is Tumor Necrosis Factor Alpha (TNF-α). Eleutherine palmifolia (Dayak onion) contains flavonoids, saponins, and tannins with antioxidant and anti-inflammatory properties. This study aimed to analyze the effect of Dayak onion extract on TNF-α levels in a DOMS rat model induced by the Forced Swimming Test (FST). The study used a randomized pre- and post-test control Group design with five groups: K–, K+, and three treatment groups receiving 50, 100, and 200 mg/200 g BW doses for 21 days. The results showed a significant decrease in TNF-α levels, with the 200 mg/200 g BW dose (P3) exhibiting the greatest effect (91.36% compared to K–) and no significant difference compared to K+. In conclusion, a 200 mg/200 g BW dose per day was the most effective in reducing TNF-α levels associated with DOMS.